Practitioner Review: Long‐term pharmacological treatment of pediatric bipolar disorder. (6th June 2014) - Díaz‐Caneja, Covadonga M.; Moreno, Carmen; Llorente, Cloe; Espliego, Ana; Arango, Celso; Moreno, Dolores
<x xml:space="preserve">Abstract</x> Background Although long‐term treatment is a core aspect of the management of children and adolescents with bipolar disorder (BD), most clinical recommendations are based on results from short‐term studies or adult data. In order to guide clinical practice, we review the efficacy and safety profile of mood stabilizers, antipsychotics, and other pharmacological strategies for the long‐term treatment of BD in pediatric patients. Methods A MEDLINE, EMBASE, Cochrane and PsycInfo search (inception through November 2013) was performed to identify prospective studies longer than 12 weeks assessing the use of pharmacological strategies for the long‐term treatment of BD in pediatric patients (0–18 years of age). Results Four randomized controlled trials (RCT) [three placebo‐controlled (assessing aripiprazole (2) and flax oil), and one head‐to‐head comparison of lithium vs. divalproex], and thirteen noncontrolled studies (six open‐label studies assessing lithium or anticonvulsants, five assessing second‐generation antipsychotics (SGAs) and four assessing combination strategies) were included in the review. Aripiprazole has shown efficacy for relapse prevention in children with pediatric bipolar disorder (PBD) 4–9 years of age in one placebo‐controlled RCT. Positive results have been reported in noncontrolled studies with quetiapine and lithium for relapse prevention, as well as with lithium, quetiapine, ziprasidone, and the combination of risperidone and divalproex or lithium for long‐term symptom reduction in PBD. The most frequently reported adverse events in children and adolescents treated with lithium and anticonvulsants are gastrointestinal and neurological, whereas use of SGAs is mainly related to weight gain and sedation. Conclusion According to the limited empirical evidence, aripiprazole can be useful for relapse prevention in children with PBD. Given the lack of consistent efficacy data, clinical decision making should be based on individual clinical aspects and safety concerns.